Fault Detection and Diagnosis of Industrial Robot Based on Power Consumption Modeling - Sabry A.H.; Nordin F.H.; Sabry A.H.; Abidin Ab Kadir M.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Data acquisition; Electric power utilization; Estimation; Fits and tolerances; Industrial robots; Manipulators; Robot applications; Signal encoding; Consumption patterns; Diagnosis techniques; Fault detection and diagnosis; Industrial robotic systems; Neural network classifier; Performance verification; Power consumption model; Wireless data acquisitions; Fault detection